The Role of Competitive Strategies in the Relationship Between Organizational Learning And Performance of Insurance Firms in Kenya - Dr. John Yabs, Sella Ogalo Ouma Prof Peter K’ Obonyo (International Journal of Scientific Research and Management (IJSRM), 2017)
Purpose: The objective of the study was to establish the moderating effect of competitive strategies on the relationship between organizational learning and firm performance. Methodology: The study used cross sectional descriptive research design. A descriptive cross-sectional design facilitated determination of relationship between or among organizational learning, competitive strategies, and performance of firms in the insurance industry in Kenya. The population of interest in this study consisted of all the 45 insurance firms offering insurance cover in Kenya. This was a census study since the population was small. Both primary and secondary data were collected and used in the study. The data analysis was done using quantitative techniques. The data collected was first summarized, categorized and coded. Descriptive statistics were used. They consisted of frequency distributions, measures of central tendency (arithmetic mean, median, and mode). Regression models were used to test the hypotheses. Results: Although the introduction of competitive strategies significantly improved the influence of organizational learning on firm performance in the case of return on assets, growth of market share and overall firm performance, in each case results did not provide sufficient evidence to support the moderation effect of competitive strategies on the relationship between organizational learning and firm performance. Further tests carried out confirmed that there is a direct and positive relationship between competitive strategies and firm performance. Unique contribution to theory, practice and policy: The study established competitive strategies as not having a moderating role in the relationship between organizational learning and firm performance, but rather as having a direct relationship with firm performance. This study brings out these interrelationships not explored before